2011
DOI: 10.1590/s1517-83822011000300028
|View full text |Cite
|
Sign up to set email alerts
|

Extended-spectrum beta-lactamase-producing bacteria isolated from hematologic patients in Manaus, State of Amazonas, Brazil

Abstract: Antibiotic therapy in hematologic patients, often weak and susceptible to a wide range of infections, particularly nosocomial infections derived from long hospitalization periods, is a challenging issue. This paper presents ESBL-producing strains isolated from such hematologic patients treated at the Amazon Hematology and Hemotherapy Foundation (HEMOAM) in the Brazilian Amazon Region to identify the ESBL genes carried by them as well as the susceptibility to 11 antimicrobial agents using the E-test method. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
1
13
0
5
Order By: Relevance
“…Over the past few years, a remarkable increase has been reported in the number of ESBL-E. Coli-associated bloodstream infections in several parts of the world (13,14). Furthermore, in cancer patients with prolonged hospitalization and with ALL who had received antibiotics for a prolonged period, the opportunity for these bacteria to cause infections enhances (14).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, a remarkable increase has been reported in the number of ESBL-E. Coli-associated bloodstream infections in several parts of the world (13,14). Furthermore, in cancer patients with prolonged hospitalization and with ALL who had received antibiotics for a prolonged period, the opportunity for these bacteria to cause infections enhances (14).…”
Section: Discussionmentioning
confidence: 99%
“…Reported frequency of ESBL producing Klebsiella species in India ranged from 14-100% [16,19]. Prevalence of ESBL producing Klebsiella around the world varies between 3%-8% to 100% [35,45]. The easiest approach to genetic detection of β-lactamases is the amplification of the whole β-lactamase (bla) gene or its parts using PCR with oligonucleotide primers that are specific for the target gene.…”
Section: Discussionmentioning
confidence: 99%
“…The quality control strain used was E. coli ATTC 25922. The susceptibility of the isolates to the antimicrobial agents was determined by means of the Kirby-Bauer disk diffusion method as described by the Clinical and Laboratory Standard Institute (Ferreira et al, 2011) Transferring 4 to 5 confirmed Salmonella colonies in a tube containing 2.5 ml sterile normal saline by means of a sterile inoculating loop to prepare a bacterial lawn. The suspension was vortexed and its turbidity compared with barium chloride (0.5 McFarland Turbidity Standard; 1.0 × 10 8 CFU/µL).…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%